Pengaruh Locus Of Control dan kinerja Auditor terhadap Dysfunctional Audit Behavior (Studi kasus pada Auditor KAP di Kota Semarang) (E-logis : Jurnal Ekonomi Logistik, 2021)
The purpose of this study was to determine the effect of Locus of Control and Auditor Performance on Dysfunctional Audit Behavior. Dysfunctional Audit Behavior as the dependent variable is the behavior of auditors in the audit process that is not in accordance with the standards as set. Locus of Control and Auditor Performance as independent variables. Locus of Control is an individual's belief about what is happening in his life. Auditor performance is the implementation of audit tasks that have been completed by the auditor within a certain time. The population in this study are auditors who work at the public accounting firm in the city of Semarang. The sampling method was using purposive sampling method. The number of samples used to support the research was 47 auditors. The data analysis technique used in this research is multiple regression analysis. The results showed that locus of control has a positive effect on dysfunctional audit behavior with a significant 0.04, individuals who have internal locus of control are in control of what happens to themselves, while individuals who have external locus of control are controlled by external forces such as luck and chance. Auditor performance has a positive effect on dysfunctiona audit behavior with a significance of 0.01. Individuals who perform work according to predetermined standards are less likely to commit acts of deviance because individuals are able to survive through their own efforts